Content Validity Evaluation of a Public Transport Service Assessment Tool Integrating Service Quality, Satisfaction, and Behavioral Intentions - Yanis, Muhammad; Saleh, Sofyan M; Achmad, Ashfa; Sari, Laina H (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
Public transportation services are essential in supporting urban mobility and sustainability. However, valid and reliable measurement tools for assessing service quality, user satisfaction, attitudes, and behavioral intentions toward public transportation remain limited. This study aimed to evaluate the content validity of a newly developed assessment instrument designed to measure those constructs. A panel of eight experts representing academia, government, and public transport practitioners was engaged to review the relevance and representativeness of each item using Content Validity Ratio (CVR) and Content Validity Index (CVI). Experts rated each item on a four-point scale of relevance. Items with a CVR value greater than 0 indicating excellent content validity. Two items were revised based on expert recommendations to improve clarity and conceptual accuracy. These findings demonstrate that the instrument is a valid and representative tool for evaluating public transport service quality and user perceptions. Further testing is recommended to establish the construct validity and reliability of the instrument for broader application in transport policy, service evaluation, and behavioral studies.